Participation and Superfluity - Wieland, Jan Willem (Journal of moral philosophy, 2020)
Why act when the effects of one’s act are negligible? For example, why boycott sweatshop or animal products if doing so makes no difference for the better? According to recent proposals, one may still have a reason to boycott in order to avoid complicity or participation in harm. Julia Nefsky has argued that accounts of this kind suffer from the so-called “superfluity problem,” basically the question of why agents can be said to participate in harm if they make no difference to it. This paper develops and responds to Nefsky’s challenge.